Analyzing the Challenges of Flood Management Policies in Bekasi City through Target Mapping Techniques - Rhianazala, Alzena; Nur Budiyanto, Muhammad; Iriani, Atrika (Universitas Indo Global Mandiri, 2026)
Purpose : This study aims to analyze the challenges in implementing flood management policies in Bekasi City through the application of target mapping techniques as a spatial-based planning and policy decision-making tool. Design/methodology/approach : This research employs a qualitative approach using a case study method focusing on flood management policies in Bekasi City. Data were collected through in-depth interviews, field observations, and document analysis of policy frameworks, flood-prone area maps, and regional planning documents. Target mapping techniques were applied to identify priority areas and key stakeholders in flood mitigation efforts. Findings : The findings indicate that flood management policy implementation in Bekasi City faces several challenges, including limited inter-agency coordination, inconsistencies in spatial planning, and suboptimal use of spatial data. The application of target mapping has proven useful in identifying flood-prone areas and prioritizing policy interventions; however, its integration into the decision-making process remains limited. Practical Implications : This study provides practical recommendations for local governments to strengthen the integration of spatial data into flood management planning, enhance cross-sectoral coordination, and optimize the use of target mapping as an evidence-based policy formulation tool. Originality/Value : This study introduces an analytical approach by utilizing target mapping techniques in the analysis of local flood management policies. The approach contributes to the development of spatial data-driven policymaking and enriches the literature on public administration and urban environmental governance.